Collaborative approaches to resolving conflict - Isenhart, Myra Warren; Spangle, Michael (Thousand Oaks, Calif. : Sage Publications, 2000)
Explains approaches to managing disputes at home, in the workplace or school, within communities, and in the international arena.
Theoretical perspectives -- Conflict in action -- Negotiation -- Mediation -- Facilitation -- Hybrids : arbitration -- Hybrids : judicial processes -- Designing systems for conflict management -- Training and education -- Summary of practitioner insights.
Includes bibliographical references and index.
Keywords: Conflict management; Dispute resolution (Law)